The long-term effects of development aid - Empirical studies in rural West Africa. - Dirk Kohnert; Georg Elwert; Thomas Bierschenk (Economics, Biannual Journal of the Institute for Scientific Co-operation, Tübingen, 1993)
This article is based on field studies in rural West Africa. It concentrates on the socio-structural effects of development aid in the long run, in contrast to numerous available evaluation reports on the short-run effects of development projects. The study reveals that superficial generalisations or condemnations of development projects, like the big farmers benefit at the expense of the smaller ones, or the men benefit at the expense of the women, do not hold up to verification. Quite to the contrary one observes a wide range of specific adapted forms by which the target groups react to the demands and offers of development projects, and thereby transform their own social structure. In short, one observes a great diversity of social self-organisation. The bureaucratic structures of the development administration do, however, unfortunately - more often than not - ignore the social dynamic of their target groups which they nevertheless sustain unconsciously. Development aid has become an important political and economic factor in most African countries. Its financial impact often exceeds that of the national budget. It contributes, therefore, significantly to the development of a bureaucratic class and of its clients: the project development degenerates into a project nationalization / bureaucratization. This contrasts vividly with the strategies of the peasants. Men and women at village level do not accept any longer the paternalistic development approach. They just select what they need out of the packages of solutions that are offered to them, while they develop their own solutions, like a variety of seeds adapted to their specific resource endowments, diversified sources of income, different strategies of accumulation and risk prevention. All this allows for a gradual evolution by variation and selection. The dynamic of the rural society is to a large extent due to a competition of different (strategic) groups, opposed to one another, about the partitioning of the cake of development aid. Normally this struggle between different vested interests is covered up by the rhetoric of development planning. Planned development has up to now proven to be to rigid, to be able to take account of the complex and subtle fabric of self organisation. Aid sometimes appears to be a second best substitute for a vision of a democratic society. This is due to the fact that the structures we are aiming for in the long run - which are to allow for open markets, an orientation of the producers at the resources and needs of the nation, and last not least, the growth of indigenous structures of self-help - would require a responsible and democratic government, as well as the guarantee of civil rights, accountability, an independent judiciary, freedom of the press, etc.; up to now, however, all these elements are still oppressed by the commando state itself, well nourished by the various forms of technical and financial aid. – – Les effets à long terme de l'aide au développement - études empiriques en Afrique de l'Ouest rural: Cet article est basé sur des études de terrain en Afrique de l'Ouest rural. Il se concentre sur les effets socio-structurelles de l'aide au développement dans le long terme, contrairement à de nombreux rapports d'évaluation disponibles sur les effets à court terme des projets de développement. L'étude révèle que des généralisations superficielles ou condamnations de projets de développement, comme les gros agriculteurs profitent au détriment des plus petits, ou les hommes bénéficient d'avantages au détriment des femmes, ne tiens pas. Bien au contraire, on observe une vaste gamme de formes adaptées spécifiques par lesquels les groupes cibles réagissent aux demandes et les offres de projets de développement, et ainsi transformer leur propre structure sociale. En bref, on observe une grande diversité de l'auto-organisation sociale. Les structures bureaucratiques de l'administration du développement, cependant, ignorent malheureusement - le plus souvent - la dynamique sociale de leurs groupes cibles dont ils soutiennent néanmoins inconsciemment. L'aide au développement est devenue un facteur politique et économique important dans la plupart des pays africains. Son impact financier dépasse souvent celle du budget national. Il contribue donc de manière significative au développement d'une classe bureaucratique et de ses clients: le développement du projet dégénère en un projet de nationalisation / bureaucratisation. Cela contraste vivement avec les stratégies des paysans. Hommes et femmes au niveau du village n'accepter plus la démarche de développement paternaliste. Ils sélectionnent tout ce dont ils ont besoin sur les paquets de solutions qui leur sont offertes, alors qu'ils développent leurs propres solutions, comme une variété de semences adaptées à leurs dotations en ressources spécifiques, diversification des sources de revenus, stratégies d'accumulation différentielles et la prévention des risques. Tout ceci permet une évolution progressive de variation et de sélection. La dynamique de la société rurale est dans une large mesure due à un concours de différents groupes (stratégiques), par opposition à un autre, sur le partage du gâteau de l'aide au développement. Normalement, cette lutte entre les différents intérêts est couvert par la rhétorique de la planification du développement. Développement planifié était jusqu'à présent trop rigide, pour être en mesure de prendre en compte le tissu complexe et subtile de l'auto-organisation. Aide semble parfois être un substitut à une vision d'une société démocratique. Cela est dû au fait que les structures que nous visons dans le long terme - qui doivent permettre l'ouverture des marchés, une orientation des producteurs à des ressources et des besoins de la nation, la croissance des structures autochtones d'auto-assistance - exigerait un gouvernement responsable et démocratique, ainsi que la garantie des droits civils, une justice indépendante, la liberté de la presse, etc . Jusqu'à présent, cependant, tous ces éléments sont toujours opprimés par l'état commando lui-même, bien nourrie par les diverses formes d'aide technique et financière.
Keywords: F35; N17; A14; R58; O2; Z1; 330; aid; ODA; Africa; Entwicklungshilfe; Subsahara-Afrika